Investigating the Effect of Nonionic Surfactant Molecular Weight on Its Drag Reduction Performance - Nurkhalida, Shahari (2013)
The major problems in transportation by pipeline are about pumping power losses due to the turbulent mode of transportation. This research is proposed to improve oil flow by using nonionic surfactant as drag reducing agent. Triton X series, one of nonionic surfactant group was selected for this study. By using three types of surfactant, Triton X- 15, Triton X-45 and Triton X-114, the effect of molecular weight between Triton X was investigated. Other variable studied are concentration (300ppm, 800ppm, 1200ppm and 1800ppm) and Reynolds number. Rotation speed of RDA used is 50rpm- 3000rpm. During the experiment, the torque reading for additive- free oil and oil with additive was recorded and used to calculate percentage of drag reduction. The data was analyzed further by plotting drag reduction versus Reynolds numbers, drag reduction versus concentration and torque versus speed. The maximum drag reduction obtained is almost 29% which occurs for oil with Triton -15 at concentration 1500ppm. As conclusion, when the concentration increases, the drag reduction increase and decreasing the molecular weight will result the increasing of drag reduction. Lastly, for all the experimental cases, the percentage of drag reduction values decreases by increasing the Reynolds number.